2020
DOI: 10.1002/aoc.5908
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: A new porous Co(II)‐coordination polymer for the chemical fixation of CO2 and treatment effect against tuberculosis by reducing the pckA expression in Mycobacterium tuberculosis

Abstract: Using the mixed-ligand method, a novel coordination polymer containing Co(II) of [Co(ditb)(tdc)] n Á5nH 2 O (1) was prepared by reacting rigid 2,5-thiophenedicarboxylic acid with flexible 1,4-di(1H-1,2,4-triazol-1-yl)butane using the slow evaporation method. Active samples of 1 (1a for short) showed good stability and the ability to capture CO 2. It can be used as a potential heterogeneous catalyst for chemical immobilization of epoxide and CO 2 to form cyclic carbonates. In addition, catalyst 1a retained its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Various experimental techniques revealed that this compound can kill M.tb efficiently by reducing pckA gene expression. 51 Gonzalez et al developed an intranasal vaccine for M.tb using another capsule with chitosan or polyarginine (shell) and an oily core. A toll like receptor-7 (TLR-7) imiquimod was encapsulated in the core and tested in vitro and in vivo.…”
Section: Worldwide Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental techniques revealed that this compound can kill M.tb efficiently by reducing pckA gene expression. 51 Gonzalez et al developed an intranasal vaccine for M.tb using another capsule with chitosan or polyarginine (shell) and an oily core. A toll like receptor-7 (TLR-7) imiquimod was encapsulated in the core and tested in vitro and in vivo.…”
Section: Worldwide Statisticsmentioning
confidence: 99%
“…The coordination polymer [Co­(ditb)­tdc] n .5 n H 2 O containing Co­(II) was prepared by mixed ligand method and its biological properties were examined in vitro and in vivo . Various experimental techniques revealed that this compound can kill M.tb efficiently by reducing pckA gene expression …”
Section: Specific Diseasesmentioning
confidence: 99%